Measuring transaction costs: from theory to practice (Journal of Economic Research & Business Administration, 2019)
The article deals with the key concept of modern institutional theory – transaction costs. Currently,the study and study of the concepts of transactions and transaction costs is given important attention.Moreover, the constantly changing conditions and mechanisms of functioning of economic systems arealso important in the study of such issues, since they inevitably lead to the possibility of the emergence,conclusion and execution of an expanded range of transactions, which is constantly updated and enrichedover time.Of particular importance in the study of issues and problems of transactions, their reflection in theaccounting, take aspects of the cost measurement and evaluation of transactions in the various processesof Contracting, in terms of contractual interactions of contractors. The existing issues of evaluation andmeasurement of transaction costs are further complicated by the presence of such characteristic featuresof transactions as the uncertainty factor in the conclusion and execution of the contract, which leadsto an increase in the uncertainty of transaction costs of various kinds, such as the costs of entering intothe market, the costs of increasing guarantees under contracts through hedging operations of the maintransaction.Also affect the specificity of different transaction costs, the possibility of separating from theirtotal set of individual elementary components, which ultimately makes them quite measurable.A transaction-based approach can provide a significant amount of information to the economic andfinancial services of an enterprise. In international practice, this is almost absolute, that is, it is clearlyunderstood that virtually every financial or accounting transaction is a transaction or an integral part ofa particular transaction.In this study of the need and the possibility of measuring transaction costs, the author relies on theConcept of integrated reporting, which combines certain types of capital, including components of socialand reputational capital.In the course of the study, a very significant conclusion is made for the accounting system: capitalizationof transaction costs of client-forming activities that form the value of reputational capital willsignificantly increase the business valuation and, at the same time, exclude from the cost of productionunusual transaction costs, which will allow only one accounting technique to increase the company’sprofit.Turning to the very essence of transaction costs, we consider it appropriate to consider them as investmentcosts involved in the process of creating business value. At the same time, we draw the reader’sattention to the fact that on this basis transaction costs should be capitalized.